"We care about others": discursive constructions of corruption vis-à-vis national/cultural identity in Indonesia's business-government relations. Issue 2 (9th December 2020) - Pertiwi, Kanti
Abstract : Purpose: This paper aims to problematize existing conceptualization of corruption by presenting alternative perspectives on corruption in Indonesia through the lens of national/cultural identity, amidst claims of the pervasiveness of corruption in the country. In so doing, the paper also sheds light on the micro-processes of interactions between global and local discourses in postcolonial settings. Design/methodology/approach: The study applies discourse analysis, involving in-depth interviews with 40 informants from the business sector, government institutions and anti-corruption agencies. Findings: The findings suggest that corruption helps government function, preserves livelihoods of the marginalized segments of societies and maintains social obligations/relations. These alternative meanings of corruption persist despite often seen as less legitimate due to effects of colonial powers. Research limitations/implications: The snowballing method of recruiting informants is one of the limitations of this paper, which may decrease the potential diversity and lead to the silencing of different stories (Schwartz-Shea and Yanow, 2013). Researchers need to contextualize corruption and study its varied meanings to reveal its social, historical and political dimensions. Practical implications: This paper strongly suggests that we need to move beyond rationalist accounts to capture the varied meanings of corruption which may be useful to explain the limited results of existing anti-corruption efforts. Social implications: This study calls for a greater use of qualitative methods to study broad social change programs such as anti-corruption from the perspective of the insiders. Originality/value: This paper contributes to the discussion of agency at the interplay between the dominant and alternative discourses in postcolonial settings. Moreover, the alternative meanings of corruption embedded in constructions of national identity and care ethics discussed in this paper offer as a starting point for decolonizing (Westwood, 2006) anti-corruption theory and practice.